Data analytics and audit quality - GAO, Ru (Institutional Knowledge at Singapore Management University, 2021)
We examine the impact of data analytics on audit quality. Using hand-collected information on data analytics skills of employees of audit firms, we find that human capital investment in data analytics improves audit quality. The analytics capability of both frontline and back-office employees contributes to audit quality. The effect is more pronounced for audit clients with complex business operations, for clients with complicated accounting estimates, and for clients that are more digitalized. Taken together, our findings suggest that an audit office’s analytics capability represents an important office attribute that can affect audit quality.